Finite element verification of the unreliability of using structural plain concrete footing under reinforced concrete footing. (December 2021) - Magbool, Hassan M.; El-Abbasy, Ahmed A.
Abstract: Globally speaking, the key role of plain concrete (PC) in shallow foundations is to produce a clean, leveled, and paved surface to put the steel rebars of reinforced concrete (RC) foundation on it. However, most Arab designers use the PC layer as an effective structural part of the entire foundation without any structural role in transmitting loads to the soil. This study aims to investigate the reliability and safety of the implemented Arab design approach. To this end, a finite element method was used, and prior to applying the finite element software, a numerical model was validated by comparing finite element results with experimental results, which were obtained from previous studies. Moreover, to examine the existing Arab approach's perilous aspects in the shallow foundation, the finite element method was extended based on the verified finite element model for further understanding of recommended and traditional approaches by comparing them with the analytical analysis obtained from previous studies. Results of the finite elements based on the conducted comparison showed good agreement compared with the experimental results. Accordingly, results of the finite element validated the results of the analytical analysis obtained from previous studies. Results showed high compressive and tensile stresses in the normally utilized traditional method in Arab countries, where the increase ratios reached up to 96% on the top surfaces of the RC footing, whereas the increase ratios reached up to 296.5% on the bottom surfaces of the PC footing. Therefore, the traditional approach is unsafe and decreases the factor of safety in designing shallow foundations. Consequently, the PC footing should not be increased by over 200 mm, and it should not be considered in structural calculations.